Microsoft® Windows® Server 2003 Delta Guide - Jones, Don (Que, 2011)
Why should new versions of mission-critical technologies mean starting from scratch? If you already know how to use Microsoft Windows Server 2000, leverage those skills to quickly become an expert on Microsoft Windows Server 2003. Microsoft Windows Server 2003 Delta Guide skips the basics and moves straight to what's new and what's changed. The result? You save time and money while preparing yourself for the next generation of Microsoft's server operating system!